2012
DOI: 10.1111/j.1365-2427.2012.02782.x
|View full text |Cite
|
Sign up to set email alerts
|

Resting egg banks can facilitate recovery of zooplankton communities after extended exposure to saline conditions

Abstract: Summary 1. Salinisation has had a major effect on the diversity of biota associated with freshwater wetlands. However, there is no information available about whether elements of the biotic communities would be able to recover if the concentration of salts within secondarily salinised wetlands was lowered to levels more typical of freshwater wetlands. 2. We tested the hypothesis that dormant eggs of zooplankton are able to persist in wetlands with elevated salinities for extended periods of time by using zoopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…While this increase in density was primarily due to proliferation of calanoid copepods under more freshwater conditions, cyclopoid copepods and cladoceran densities also increased. In two interrelated mesocosms studies, Nielson et al [57] [58] reported that with salinity increases (up to 15,000 mg L −1 sea salt), the developing zooplankton communities diverged greatly from the original freshwater species pool and ultimately resulted in domination by a small number of salt-tolerant species. As salinity levels in these artificial ponds were subsequently decreased (<2500 mg L −1 sea salt), zooplankton communities became increasingly similar with more taxa representative of freshwater systems.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…While this increase in density was primarily due to proliferation of calanoid copepods under more freshwater conditions, cyclopoid copepods and cladoceran densities also increased. In two interrelated mesocosms studies, Nielson et al [57] [58] reported that with salinity increases (up to 15,000 mg L −1 sea salt), the developing zooplankton communities diverged greatly from the original freshwater species pool and ultimately resulted in domination by a small number of salt-tolerant species. As salinity levels in these artificial ponds were subsequently decreased (<2500 mg L −1 sea salt), zooplankton communities became increasingly similar with more taxa representative of freshwater systems.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Some authors suggest that in brackish and other transitional waters species richness is lower than in freshwater and marine habitats (Remane, 1934). Previously published data show that freshwater zooplankton species, mostly rotifers and cladocerans, show low tolerance to increasing salinity (Hart et al, 1991; Boronat et al, 2001;Nielsen et al, 2003Nielsen et al, , 2012North and Houde, 2003;Waterkeyn et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Hart et al (1991) showed that freshwater Cladocera are less tolerant to salinities above 1000 mg.L x1 (2000 mS.cm x1 ). Furthermore, Nielsen et al (2012) reported that average densities of the zooplankton community increased at salinities below 2500 mg.L x1 (4000 mS.cm x1 ), otherwise were < 1 ind.L x1 . The common taxa at salinities above 2500 mg.L x1 were Cyclopoida and copepod nauplii, Lecane spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For monogonont rotifers, resting eggs is the end-product of sexual reproduction and can survive at extreme environmental conditions such as low temperature or aridity (Pourriot and Snell, 1983;Nielsen et al, 2012;Ricci, 2001). Its production process encompasses the full-life cycle of rotifer, which can thus avoid the limitations of partial life-cycle toxicity tests if resting eggs are chosen as testing endpoint (Preston and Snell, 2001).…”
Section: Introductionmentioning
confidence: 99%